Afterschool quality. Issue 144 (December 2014) - Smith, Charles; Akiva, Tom; McGovern, Gina; Peck, Stephen C.
Abstract : This chapter discusses efforts to define and improve the quality of afterschool services, highlighting areas of agreement and identifying leading‐edge issues. We conclude that the afterschool field is especially well positioned to deliver high‐quality services and demonstrate effectiveness at scale because a strong foundation has been built for continuous improvement of service quality.